Efficacy and tolerability of a novel food supplement (Turbofer®) containing microencapsulated iron in liposomal form, in female iron deficiency anaemia - Pleşea-Condratovici, A.; Pleşea-Condratovici, C.; Rosoga, N.; Nedelcu, N. (Progress in Nutrition, 2015)
Introduction: According to the WHO, iron deficiency and related iron deficiency anaemia (IDA) are the most prevalent nutritional disorders worldwide. Anaemia occurs in all age racial and ethnic groups. The goal of treatment of anaemia is to increase the amount of oxygen that blood can carry by raising the red blood cell count and/or Haemoglobin level and to treat the underlying cause of the anaemia. Objectives: To evaluate the efficacy of a novel food supplement, Turbofer®, formulated with microencapsulated iron in liposomal form, on the capacity to raise Haemoglobin and Haematocrit levels, the most important indicators of IDA in the study population. Tolerability was also evaluated. Materials and methods: 30 subjects, post-menopausal females, were enrolled in an open multi-center study. The subjects were administered Turbofer®, twice daily, independently by food intake, for eight weeks. The subjects included suffered from iron deficiency anaemia (Haemoglobin < 11,5 g/dl) and had already been treated with other iron supplements or drugs experiencing side effects. Laboratory tests were performed at visit 1 (baseline) and visit 2 (eight weeks after beginning treatment) together with registration of side effects (signs and symptoms) caused by previous and actual iron treatments by means of Gastrointestinal Sign and Symptoms Score. Results: The mean level of Haemoglobin at the beginning of the study was 10.65 ± 0.59 and 12.77 ± 1.08 at the end of the study. This increase is highly significant (p<0.00001). Also the value of Haematocrit showed a highly significant rise (p<0.00001) from 33.32 ± 2.78 to 38.95 ± 2.92 in the population study. There were no dropouts and Turbofer® was very well tolerated by all subjects, with a marked decrease of the gastrointestinal symptoms compared to previous iron treatments. Conclusion: 8 weeks of Turbofer® daily supplementation significantly rise the Haemoglobin and the Haematocrit level. Microencapsulated iron in liposomal form improves iron absorption leading to high bioavailability: as a result, Haemoglobin increase quickly and Turbofer® treatment does not cause the stomach upset and constipation associated with the use of other iron tablets, that is often responsible for the poor compliance.